2022
DOI: 10.7759/cureus.30404
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Child Eye Healthcare Among Parents in Aseer Region, Saudi Arabia

Abstract: Background: The majority of causes of childhood blindness are preventable and treatable. There are an estimated 1.4 million blind children worldwide, with roughly three-quarters of them living in developing countries. In most low-income countries, school-age children account for 20%-30% of the total population. Aim: To evaluate parents' knowledge, attitudes, and practices related to pediatric eye medical services in Saudi Arabia's Aseer region.Methodology: A descriptive cross-sectional approach was used target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…Parents with bachelor's degrees and those aged 36-45 years possessed better knowledge than the others, which was similar to the results of another study [25]. Expectedly, a higher education level and a younger age are usually associated with more opportunities to learn and read about health issues.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Parents with bachelor's degrees and those aged 36-45 years possessed better knowledge than the others, which was similar to the results of another study [25]. Expectedly, a higher education level and a younger age are usually associated with more opportunities to learn and read about health issues.…”
Section: Discussionsupporting
confidence: 86%
“…Another study done in Aseer revealed that 48.5% (n = 436) of the respondent parents accompanied their children to eye examinations. Furthermore, for parents who never take their children to an eye examination, the most common reason is that they assert that their children can see well [25]. Therefore, it is very important to design and implement health education campaigns to discuss the advantages of regular eye examinations and early detection of any VI among children and warn them about the probable complications resulting from discovering eye diseases in their late stages.…”
Section: Discussionmentioning
confidence: 99%
“…The specific disorder included hypertension (44%), valvular heart disease (26%), dyslipidemia (18%), pericarditis (6%), and heart failure (6%). In comparison, a similar local study reported a prevalence of cardiovascular complications at 18%, with specific diseases including pericarditis and myocarditis (14%), endocarditis (11%), myocardial infarction (20%), coronary artery disease (38%), and valvular heart diseases (14%) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ocular allergy (OA), also known as allergic conjunctivitis (AC), is a wide category including a variety of illnesses in which an abnormal conjunctival inflammation occurs in reaction to allergens that are typically innocuous [ 1 ]. It is one of the most common ocular surface conditions treated by primary eye care professionals [ 2 ].…”
Section: Introductionmentioning
confidence: 99%